Widening the frontiers of elastography in biomechanics: simultaneous muscle elasticity measurements at high-sample rate with surface wave elastography - Grinspan, Gustavo A.; Oliveira, Liliam Fernandes De; Brandao, Maria Clara; Benech, Nicolás (Frontiers in Physics, 2024)
In recent years, elastography has become a widely accepted methodology to assess the longitudinal shear elastic modulus of skeletal muscle. Ultrasound shear wave elastography is the gold standard used for such a purpose. However, its low sample rate (1-2 Hz) and the impossibility of being used in several muscles simultaneously limit potential biomechanical applications. In this work, we overcome such limitations by using a surface wave elastography method (NU-SWE). Methods: The NU-SWE comprises a wearable device suitable for measuring several muscles simultaneously. Elasticity can be measured at high-frequency rates ( 15Hz), by propagating several pulse trains of low-frequency ( 100 Hz) superficial waves separated by a short time interval. These pulses propagate along the medium surface and are recorded by a linear array of vibration sensors placed on the skin of each measured muscle. In this context, this work carried out a proof of concept, showing how NU-SWE enables performing experimental protocols previously impracticable with ultrasound elastography. Thus, we measured the longitudinal shear elasticity of the biceps brachii and brachioradialis muscles simultaneously at 15 Hz during isometric elbow flexions exerted at different torque development rates. Furthermore, for comparison, we measured the electromyographic activity of both muscles. Results: Our results show that the maximum elasticity reached by the brachioradialis increases with contraction rate, while the biceps brachii behaves inversely. Discussion: This study provides new insights concerning muscle synergism, evidenced by changes in muscle elasticity during torque production. More generally, it shows that NU-SWE could help widen elastography-driven research in biomechanics.